Suppression of FVIII-Specific Memory B Cells by Chimeric BAR Receptor-Engineered Natural Regulatory T Cells - Pohl, Alessandra De Paula; Venkatesha, Shivaprasad H.; Zhang, Ai-Hong; Scott, David W. (Frontiers in Immunology, 2020)
Anti-drug antibody formation poses tremendous obstacles for optimal treatment of hemophilia A (HA). In this study, we sought to utilize chimeric receptor-modified natural regulatory T cells (Tregs) to target FVIII-specific memory B cells, which are responsible for persistent anti-FVIII neutralizing antibodies (inhibitors) in HA patients. Thus, CD4+CD25hiCD304+ natural Tregs were FACS sorted from naïve C57BL/6 mice and retrovirally transduced to express a chimeric B-cell antibody receptor (BAR) containing the immunodominant A2 domain of FVIII. Plasmablast-depleted (CD138neg) splenocytes from FVIII immunized FVIII-knockout HA mice served as the source for FVIII-specific memory B cells, which were specifically stimulated in vitro with FVIII and enumerated in a B-cell ELISPOT assays. Adding A2-BAR Tregs (1 per 150 splenocytes), but not conventional T cells, to the CD138- splenocytes significantly suppressed the formation of anti-FVIII antibody secreting cells (ASC), compared to the non-relevant OVA-BAR Tregs control group. The observation that A2-BAR Tregs can suppress the response to FVIII suggests that bystander suppression can occur in the local milieu in this system. Transwell experiments confirmed that the suppression was contact-dependent. Moreover, even in the presence of antibodies to FVIII (so-called inhibitors), similarly prepared CD4+CD25hiCD127low A2-BAR human natural Tregs completely suppressed polyclonal anti-FVIII ASC formation. In conclusion, we demonstrated in vitro that FVIII domain-expressing BAR Tregs could efficiently target and suppress FVIII-specific memory B cells.